Hypoglycaemia Metabolic Gene Panel Testing - Maiorana, Arianna; Lepri, Francesca Romana; Novelli, Antonio; Dionisi-Vici, Carlo (Frontiers in Endocrinology, 2022)
Hypoglycemia is an important cause of morbidity in children and is associated with a large number of inborn errors of metabolism. Mutations in different genes coding for enzymes, transporters and transcription factors lead to impairment of glucose homeostasis from different biochemical pathways involving insulin secretion, fatty acid oxidation, ketone bodies formation and degradation, glycogen metabolism, fructose and galactose metabolism, branched chain aminoacids and tyrosine metabolism, mitochondrial function and glycosylation proteins mechanisms. Historically, genetic analysis consisted of highly detailed molecular testing of nominated single genes. However, more recently, the genetic heterogeneity of these conditions imposed to undertake broad molecular testing on an individual patient basis within a clinically useful timeframe via exome sequencing. Indeed, the establishment of a rapid diagnosis allows prompt targeting of specific nutritional and pharmacological therapies. The biochemical and clinical phenotype are critical to drive the molecular analysis toward those clusters of genes involved in specific pathways and address data interpretation regarding the finding of possible disease-causing variants at first reported as variants of uncertain significance in known genes or the discovery of new disease genes. Also, the trio’s analysis allows genetic counseling for recurrence risk and prenatal diagnosis in eventual future pregnancies. Furthermore, this approach with new generation sequencing techniques is challenging our previous concepts of existing genetic diagnoses, when apparently pathogenic variants are found in well-described disease genes but the patient’s clinical picture falls outside the boundaries of the expected phenotype. Multidisciplinary input and collaboration are increasingly key for addressing the analysis and interpreting the significance of the genetic results, allowing rapidly their translation from bench to bedside.